2019
DOI: 10.35371/aoem.2019.31.e1
|View full text |Cite
|
Sign up to set email alerts
|

Association between shift work and hyperhomocysteinemia in male workers

Abstract: BackgroundShift work is associated with a higher risk of cardiovascular diseases. Here, we sought to assess the relationship between shift work and plasma homocysteine levels. Determining the correlations between shift work and homocysteine levels may provide a better understanding of the mechanisms underlying cardiovascular diseases.MethodsThis study was performed using data from routine health examinations of steel workers in 2017. In total, 431 male workers (70 daytime workers and 361 shift workers) employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…Among the previous studies reporting similar results are the aforementioned study by Kang et al 11 as well as others on the correlation between shift work and the serum homocysteine level. In Martins et al, 27 a study conducted on 30 Brazilian shift work bus drivers and 22 control subjects, the serum homocysteine level was significantly higher in shift workers than in the control (18.57 vs. 9.43 μmol).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Among the previous studies reporting similar results are the aforementioned study by Kang et al 11 as well as others on the correlation between shift work and the serum homocysteine level. In Martins et al, 27 a study conducted on 30 Brazilian shift work bus drivers and 22 control subjects, the serum homocysteine level was significantly higher in shift workers than in the control (18.57 vs. 9.43 μmol).…”
Section: Discussionsupporting
confidence: 75%
“…Of note is that the serum homocysteine level could be higher in shift workers than in non-shift workers as shift workers are more susceptible to CVD. In Kang et al, 11 a study on the workers at a steel manufacturing company in South Korea, the serum homocysteine level was shown to be significantly higher in male shift workers with a certain length of work than in male day workers. However, no study has yet reported on the correlation between serum homocysteine level and CVD risk of female workers in South Korea.…”
Section: Introductionmentioning
confidence: 99%
“…The second most referenced subcategory was lifestyles (n = 19), where eating habits stood out [58][59][60][61][62][63][64][65][66], followed by physical exercise [66][67][68], alcoholism [67,69], smoking [67,68], and health behaviors [71,72]. The cardiovascular system references (n = 17) were divided into cardio-metabolic risk factors [65,[73][74][75][76][77][78][79][80][81][82], hypertension [81,[83][84][85], and heart rate [34,86]. The subcategory related to mental health included 16 references, highlighting the study of aspects such as anxiety and depression [37, 50,55,87,88] and burnout [41,84,89].…”
Section: Resultsmentioning
confidence: 99%